Boiling Histotripsy Ablation of Renal Cell Carcinoma in the Eker Rat Promotes a Systemic Inflammatory Response - Schade, George R.; Wang, Yak-Nam; D'Andrea, Samantha; Hwang, Joo Ha; Liles, W. Conrad; Khokhlova, Tatiana D. (Ultrasound in medicine & biology, 2019)
Boiling histotripsy (BH) is an experimental focused ultrasound technique that produces non-thermal mechanical ablation. We evaluated the feasibility, short-term histologic effects and the resulting acute inflammatory response to BH ablation of renal cell carcinoma (RCC) in the Eker rat. Genotyped Eker rats were monitored for de novo RCCs with serial ultrasound (US) imaging. When tumors were ≥8 mm, rats underwent ultrasound-guided extracorporeal ablation of the tumor with BH, a pulsed focused US technique that produces non-thermal mechanical ablation of targeted tissues, or a sham US procedure. Treatments targeted approximately 50% of the largest RCC with a margin of normal kidney. BH treated rats were euthanized at 1 (n = 4) or 48 (n = 4) h, and sham patients (n = 4) at 48 h. Circulating plasma cytokine levels were assessed with multiplex assays before and at 0.25, 1, 4, 24 and 48 h following treatment. Kidneys were collected and processed for histologic assessment, immunohistochemistry and intrarenal cytokine concentration measurements. For statistical analysis Student's t-test was used. US-guided BH treatment was successful in all animals, producing hypoechoic regions within the targeted volume consistent with BH treatment effect. Grossly, regions of homogenized tissue were apparent with evidence of focal intra-parenchymal hemorrhage. Histologically, BH produced a sharply demarcated region of homogenized tumor and non-tumor tissue containing acellular debris. BH treatment was associated with significantly increased relative concentration of plasma TNF versus sham treatment (p < 0.05) and transient elevations in high-mobility group box 1 (HMGB1), IL-10 and IL-6 consistent with acute inflammatory response to trauma. Intrarenal cytokine concentrations followed the same trend. At 48 h, enhanced infiltration of CD8+ T cells was observed by immunohistochemistry in both the treated and un-treated contralateral RCC/kidneys in BH-treated animals versus sham treatment. BH treatment was well tolerated with transient gross hematuria and a perinephric hematoma developing in one subject each. The study demonstrates the feasibility of BH ablation of de novo RCC and suggests activation of the acute inflammatory cascade following treatment that appears to stimulate CD8+ T cell infiltration of both treated and untreated tumors. Longer duration chronic studies are ongoing to characterize the longevity and robustness of this response.